Distributed Convolutional-Coded Differential Space-Time Block Coding - Soon Xin Ng; Yang Wang; Hanzo, Lajos (2010 IEEE 71st Vehicular Technology Conference, 2010)
A low complexity distributed coding scheme is proposed for communications over Rayleigh fading channels. Convolutional Coding (CC) assisted Differential Phase-Shift Keying (DPSK) modulation is employed at the source node for conveying the source signals to two relay nodes as well as to the destination node during the first transmission period. Iterative detection exchanging extrinsic information between the DPSK demapper and CC decoder is carried out at each relay node in order to recover the source signals. Then, the CC-encoded bits are re-encoded by the two relays to generate Differential Space-Time Block Coding (DSTBC) symbols for transmission to the destination node during the second transmission period. At the destination node, iterative decoding exchanging extrinsic information is invoked between the DPSK demapper and the concatenated CC-DSTBC decoder, where the later is viewed as a single amalgamated decoder. The relay and destination nodes do not have to estimate the channel's fading coefficients due to the employment of DPSK and DSTBC schemes. Our design requires only two decoding iterations between the DPSK and CC decoders at each relay in order to further reduce the complexity of the relay nodes. Our distributed coding scheme assisted by two low-complexity relay nodes outperforms the non-cooperative benchmarker scheme by about 8 dBs, when aiming for a bit error ratio of 10 -5 .